Analysis of energy consumption and forecasting sectoral energy demand in Pakistan. (15th October 2021) - Ali, Zulfiqar; Shaikh, Faheemullah; Kumar, Laveet; Hussain, Sadam; Memon, Zubair Ahmed
The long-term forecasting of energy consumption has attained significant importance in fundamental research to provide sustainable solutions to the sectoral energy issues. An analysis of various factors that spur the overall and sectoral energy consumption has been modelled using logarithmic mean divisia index (LMDI) based on long-term energy alternatives planning (LEAP). The LMDI factors such as scale, structure and efficiency effects have been modelled in LEAP to forecast the overall and sectoral energy consumption. Various scenarios based on estimated LMDI factors have been modelled. It was observed that the scale and structure effects have generally caused an increase whereas the efficiency effect has caused a decrease in the overall and sectoral energy consumption. Furthermore, it was observed that the results reveal that the total energy consumption may reach 2, 048, 017.38 MTOE in 2050. Energy consumption in agriculture, industrial and services sector may reach 17, 327.29 MTOE, 1, 759, 372.72 MTOE, 271, 317.37 MTOE in 2050, respectively. From these findings, it is clear that the industrial sector consumes 86% of total energy. These results can help develop various policy guidelines for better management and operation of the energy sector in Pakistan.